Comparative effects of aerobic walking and resistance exercise on cognitive function in older adults: A quasi-experimental study - Fandrian, Ganang; Dowes, Muchsin; Liskustyawati, Hanik (Journal Sport Area, 2025)
Background: Cognitive decline poses a major threat to independence and quality of life in older adults. Exercise is widely recognized as a non-pharmacological approach to preserve cognition, yet many studies overlook baseline cognitive status and seldom compare aerobic and resistance modalities. This gap limits clarity on which type of exercise is more effective in maintaining cognitive health. Research Objectives: This study aimed to determine the effects of aerobic walking exercise (AWE) and resistance exercise (RE) on cognitive function in older adults. Methods: A quasi-experimental pre-test/post-test design was conducted with 45 participants (23 males, 22 females; aged 60–69 years). Using ordinal pairing to balance baseline scores, participants were assigned to AWE (n = 22) or RE (n = 23). Both groups completed 24 exercise sessions over eight weeks (three sessions per week). Cognitive function was assessed with the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) under single-blind conditions. Statistical analyses included paired t-tests (within-group) and one-way ANCOVA (between-group) at a 5% significance level. Findings/Results: Both interventions significantly improved cognitive function (P < 0.001). However, RE produced greater gains (mean increase 2.21 points, 11.99%) than AWE (mean increase 1.27 points, 7.06%), with a moderate effect size (ƞp² = 0.110; P < 0.05). Conclusion: Resistance exercise yields superior improvements in cognitive function compared to aerobic walking among older adults. These findings highlight the importance of incorporating resistance-based programs in community health initiatives, provided safety principles are ensured. Future research should extend to larger and more diverse populations, examine long-term effects through longitudinal designs, and evaluate applicability in individuals with comorbid conditions.